Validation of a conceptual model to find adequate organisational structures - Silva, J. (Implementation ? realizing operations management knowledge, XVI international annual conference of the EurOMA, 2009)
The reported test and development of a conceptual model showed how methods of science and theory might help practice. So, a validation exercise was conducted by discussing the structural effectiveness hypotheses and by using ten frameworks of respected researchers, following SSM guidelines. Research outcomes concern a credible audit tool to operationalise a structured debate about change, as regards PPC relevance. Then, a medium range theory to assess structure adequateness was proposed, based on finding relevant choices for all design parameters of the structure, beyond PPC.